Tourist Attraction and Prices on Interest in Visiting with Media Promotions at Ubalan Waterpark Mojokerto - kusumawati evi; Mochamad Saleh (Jurnal Manajemen Sains dan Organisasi, 2023)
Purpose - The purpose of this study is to examine the direct and indirect effects oftourist attraction and prices on tourist interest in visiting through promotion. Thisresearch method is quantitative with path analysis.Design/methodology/approach - The research respondents were 100 tourists whovisited Ubalan Waterpark Mojokerto. This study used an instrument in the form of aquestionnaire which was processed using the SPSS program.Findings - The results of the study show that tourist attraction and price have asignificant effect on promotion; tourist attraction and promotion have a significanteffect while price has no effect on visiting interest. Tourist attractiveness has anindirect effect on visiting intentions through promotions, while prices have notproven to have a significant indirect effect through promotions on tourists' visitingintentions